Streptococci and the complement system: interplay during infection, inflammation and autoimmunity. Issue 16 (19th August 2020) - Syed, Shahan; Viazmina, Larisa; Mager, Riccardo; Meri, Seppo; Haapasalo, Karita
Abstract : Streptococci are a broad group of Gram‐positive bacteria. This genus includes various human pathogens causing significant morbidity and mortality. Two of the most important human pathogens are Streptococcus pneumoniae (pneumococcus) and Streptococcus pyogenes (group A streptococcus or GAS). Streptococcal pathogens have evolved to express virulence factors that enable them to evade complement‐mediated attack. These include factor H‐binding M ( S. pyogenes ) and pneumococcal surface protein C (PspC) ( S. pneumoniae ) proteins. In addition, S. pyogenes and S. pneumoniae express cytolysins (streptolysin and pneumolysin), which are able to destroy host cells. Sometimes, the interplay between streptococci, the complement, and antistreptococcal immunity may lead to an excessive inflammatory response or autoimmune disease. Understanding the fundamental role of the complement system in microbial clearance and the bacterial escape mechanisms is of paramount importance for understanding microbial virulence, in general, and, the conversion of commensals to pathogens, more specifically. Such insights may help to identify novel antibiotic and vaccine targets in bacterial pathogens to counter their growing resistance to commonly used antibiotics. Abstract :